2011
DOI: 10.1590/s1415-52732011000200010
|View full text |Cite
|
Sign up to set email alerts
|

Alimentação fora do domicílio de consumidores do município de Campinas, São Paulo

Abstract: ObjetivoAvaliar, em uma amostra não probabilística de indivíduos, a frequência de consumo de refeições realizadas fora do domicílio e os tipos de estabelecimentos mais utilizados para realizar o almoço. MétodosEntrevistou-se, em janeiro de 2006, por meio de questionário pré-testado, uma amostra por probabilística de 250 consumidores -125 do sexo masculino e 125 do sexo feminimo -, adultos, residentes no município de Campinas. Para identificar diferenças significativas entre a frequência com que o consumidor co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 16 publications
0
5
0
8
Order By: Relevance
“…In a study in the city of São Paulo, Southeastern Brazil, lunch was the meal most frequently eaten outside of the home. 22 This analysis does not allow consumption to be analyzed according to type of meal, although the majority of food eaten outside the home was consumed between 12 and 2 PM.…”
Section: Discussionmentioning
confidence: 99%
“…In a study in the city of São Paulo, Southeastern Brazil, lunch was the meal most frequently eaten outside of the home. 22 This analysis does not allow consumption to be analyzed according to type of meal, although the majority of food eaten outside the home was consumed between 12 and 2 PM.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have analyzed eating location to compare meals made at home and away from home, types of restaurants, or consumed foods [18][19][20][21] . Even Brazilian studies have failed to analyze meals consumed at work cafeterias.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that consumers use a variety of informational signs concerning food safety when they judge and choose restaurants to eat in. In general, the question of the hygienic conditions of the ambient, utensils and workers has been reported as a factor to be considered in this selection (Fatimah, Boo, Sambasivan, & Salleh, 2010;Sanches & Salay, 2011;Sienny & Serli, 2010). However, consumer perception can frequently be equivocated due to a lack of information concerning the potential risks of restaurant practices.…”
Section: Introductionmentioning
confidence: 99%